Re-defining pT4b buccal mucosa squamous cell carcinoma: Looking beyond palliation in select patients - Prateek V. Jain; Kapila Manikantan; Gary M. Clark; Indranil Mallick; Sanjoy Chatterjee; Indu Arun; Paromita Roy; Lateef Zameer; Pattatheyil Arun (Oral Oncology Reports)
Objectives: Reports in the last 2 decades suggest that selected patients with masticator space invasion can be treated surgically with reasonable survival. This study is an attempt to identify prognosticators for disease free (DFS) and overall survival (OS) in surgically treated pT4 buccal mucosa squamous cell carcinoma (BMSCC) patients. Material and methods: The cohort for this retrospective study comprised 213 patients with pT4a/b BMSCC, treated with curative intent surgery from August 2011 through December 2019. Depending upon masticator space invasion (MSI) patients were divided into 3 groups viz. pT4a, involvement of masseter and/or medial pterygoid (Low MSI) and involvement of lateral pterygoid and/or temporalis (High MSI). Results: The median follow-up in this study was 45 (2–123) months. The 5-year DFS was 53 %, 42 % and 21 % for pT4a, Low MSI and high MSI groups, respectively. The 5-year OS was 68 %, 43 % and 21 % for these three groups. The MSI (HR 1.5, p = 0.113 for Low MSI, HR 2.98, p < 0.001 for high MSI), perineural invasion (PNI) (HR 2.17, p = 0.001) and extranodal extension (ENE) (HR 2.74, p = 0.001) predicted poor DFS on multivariate analysis. OS was worse in patients with MSI (HR 1.86, p = 0.020 for Low MSI, HR 3.46, p < 0.001 for high MSI), PNI (HR 2.48, p < 0.001) and ENE (HR 3.02, p = 0.001) on multivariate analysis. Adjuvant treatment improved both OS and DFS. Conclusion: Select patients with masticator space involvement can benefit from aggressive treatment. Radiation with or without chemotherapy in adjuvant setting can further improve prognosis in these patients.